Psychometric characteristics of the "General Oral Health Assessment Index (GOHAI) » in a French representative sample of patients with schizophrenia - Frederic Denis; Mohamad Hamad; Benoit Trojak; Stéphanie Tubert-Jeannin; Corinne Rat; Jean-François Pelletier; Nathalie Rude (BMC, 2017)
Abstract Background The "General Oral Health Assessment Index" (GOHAI) was widely used in clinical or epidemiological studies worldwide, as it was available for use in different languages. Therefore, the aim of this study was to evaluate the psychometric characteristics of the GOHAI in a representative sample of patients with schizophrenia. Methods A total of 90 schizophrenic patients (in-patients and out-patients) were recruited from the participants of the "buccodor study" (NCT02167724) between March and September 2015. They were selected using a random stratified sampling method according to their age, sex, or residential area (urban/rural area). GOHAI validity (construct, predictive, concurrent and known group validity) and internal consistency (reliability) were tested. Test-retest reliability was evaluated in 32 subjects. Results The mean age was 47.34 (SD = 12.17). Internal consistency indicated excellent agreement, with a Cronbach's α $$ α $$ value of 0.82 and average inter-item correlation of 0.65. Intraclass correlation coefficients for test-retest reliability with 95% confidence intervals were not significantly different (p > 0.05). Construct validity was supported by three factor that accounted for 60.94% of the variance observed. Predictive validity was corroborated as statistically significant differences were observed between a high GOHAI score, which was associated with self-perceived satisfaction with oral health, lower age and high frequency of toothbrushing. Concurrent validity was corroborated as statistically significant relationships were observed between the GOHAI scores and most objective measures of dental status. For known group validity, they was no significant difference of the mean GOHAI score between out or in-patients (p > 0.05). Conclusion Acceptable psychometric characteristics of the GOHAI could help caregivers to develop ways to improve the Oral Health related Quality Of Life of schizophrenic patients. Trial registration Clinical Trials Gov NCT02167724 . Date registered 17 June, 2014.